THE IMPLEMENTATION OF REFLECTION-BASED ACADEMIC SUPERVISION IN ENHANCING TEACHERS’ PROFESIONALISM AT AN INDONESIAN PUBLIC ELEMENTARY SCHOOL - Istiqomah; Zayyinul Firdaus; Nur Khomsin; Soedjono (SOSIOEDUKASI, 2026)
This study aimed to describe the implementation of reflection-based academic supervision in enhancing teachers’ professionalism at SD Negeri Batursari 5, Mranggen Subdistrict, Demak Regency. A qualitative descriptive approach was employed to obtain an in-depth understanding of the supervision process and its impact on teachers’ professional development. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal and teachers. The findings reveal that reflection-based academic supervision was implemented through systematic stages, including supervision planning, classroom observation, reflective dialogue, and follow-up coaching. Reflective supervision encouraged teachers to critically evaluate their teaching practices, improve instructional planning, and strengthen pedagogical competence. The study also identified several challenges, such as time constraints, teachers’ readiness for self-reflection, and limited follow-up programs. Nevertheless, reflective supervision contributed positively to fostering teachers’ professional awareness, openness to feedback, and commitment to continuous improvement. This study concludes that reflection-based academic supervision is an effective strategy for enhancing teacher professionalism when implemented collaboratively and sustainably within a supportive school culture.